Staff Development Programme and Job Performance in Kuala Muda/Yan - May, Khor Guat Sim (1998)
The purpose of this study is to investigate the perception of secondary school teachers on the effects of staff development programme on the their job performance. The study was carried out at 10 selected secondary schools in the Kuala Muda/Yan district in Kedah. 322 respondents were randomly chosen from the 10 selected schools to take part in the survey using a 41-item questionnaire. The results of the survey were analysed using the Pearson correlation method, t-test and analysis of variance in SPSS. The analysis showed that there is very significant relationship between the perception of teachers on job performance and staff development. However, only a moderate correlation of 0.6065 was obtained between the perception of teachers on job performance and staff development programme. Job performance could be affected by other factors such as motivation, ability, traits, role perceptions, rewards and reinforcers. The salary movement in the New Remuneration System for government employees was found to be very significantly related to the perception of teachers on staff development programme and job performance. The perception of the teachers on their job performance and staff development programme were found to be significantly related to the number of inservice and in-house training programmes attended by the teachers. The results of the analysis of variance proved that the perception of staff development programme and job performance of the teachers were found to be very significantly related to the position held by the teachers. In contrast, it was found that the demographic factors of gender, age, marital status, academic qualifications and length of service have no effect on the teachers’ perception of staff development programme not job performance. Suggestions for future staff development programme and further study were proposed.